2018
DOI: 10.1371/journal.pone.0191795
|View full text |Cite
|
Sign up to set email alerts
|

A comparative work on the magnetic field-dependent properties of plate-like and spherical iron particle-based magnetorheological grease

Abstract: In this study, a new magnetorheological (MR) grease was made featuring plate-like carbonyl iron (CI) particles, and its magnetic field-dependent rheological properties were experimentally characterized. The plate-like CI particles were prepared through high-energy ball milling of spherical CI particles. Then, three different ratios of the CI particles in the MR grease, varying from 30 to 70 wt% were mixed by dispersing the plate-like CI particles into the grease medium with a mechanical stirrer. The magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Furthermore, it is observed that the bidisperse MRG has an enhanced LVE region of the mono-shaped MRG with the plate-like CI particles, which in turn indirectly increases the storage modulus. Based on authors’ previous studies, the average diameter for the plate-like and spherical CI particles are 6.2 µm and 5 µm, respectively [33]. Theoretically, the small-diameter spherical CI particles are inclined to fill the void between the larger plate-like CI particles in the grease medium [42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is observed that the bidisperse MRG has an enhanced LVE region of the mono-shaped MRG with the plate-like CI particles, which in turn indirectly increases the storage modulus. Based on authors’ previous studies, the average diameter for the plate-like and spherical CI particles are 6.2 µm and 5 µm, respectively [33]. Theoretically, the small-diameter spherical CI particles are inclined to fill the void between the larger plate-like CI particles in the grease medium [42].…”
Section: Resultsmentioning
confidence: 99%
“…The spherical CI particles with OM grades were purchased from BASF, Germany with the average diameter in the range of 3.9 to 5.2 µm and density of 7.874 g cm −3 . The plate-like CI particles were prepared using a high-energy rotary ball mill machine used in previous works [8,33]. The spherical CI particles were milled with the presence of a zirconia ball as the grinding medium at a ball-to-powder ratio of 20:1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is fast, reversible, and controllable (Hardy, 1951;Jacob, 1951;Carlson and Spencer, 1996). Researches indicate that MR fluid is typically characterized by the shear stress, and apparent viscosity changing with the external shear rate and magnetic field intensity, and that the type, saturation magnetization, surface characteristic, size, and morphology of magnetizable particles (Jolly et al, 1999;Hato et al, 2011;Susan-Resiga and Vékás, 2014;Liu et al, 2015;Vereda et al, 2016;Mohamad et al, 2018) have a great influence on the mechanical properties of the MR material. Due to the apparent sedimentation of MR fluid, MR grease has been proposed, improving its anti-sedimentation greatly (Zhu, 2006;Hu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The rotational shear experiment was surveyed in the shear rate range of 0.1 to 100 s −1 . When each test finished, the MR grease samples were degaussed and a new magnetic field was applied [31]. Through the Bingham viscoplastic model, the dynamic yield stress values for the MR grease samples were obtained by calculating shear stress versus shear rate curves to zero shear rate and searching for the point of intersection with the vertical axis [11,18], as show in Figure 3.…”
Section: Methodsmentioning
confidence: 99%